Two rare autosomal recessive neurological disorders identified by combined genetic approaches in a single consanguineous family with multiple offspring - Süsgün, Seda; Yücesan, Emrah; Göncü, Beyza; Hasanoğlu Sayın, Sevde; Kına, Ümit Yaşar; Özgül, Cemil; Düzenli, Ömer Faruk; Kocatürk, Özcan; Çalık, Mustafa; Özbek, Uğur; Uğur İşeri, Sibel Aylin (My University, 2024)
Introduction: Neurodevelopmental disorders (NDDs) refer to a broad range of diseases including developmental delay, intellectual disability, epilepsy, autism spectrum disorders, and attention-deficit/hyperactivity disorder caused by dysfunctions in tightly controlled brain development. The genetic backgrounds of NDDs are quite heterogeneous; to date, recessive or dominant variations in numerous genes have been implicated. Herein, we present a large consanguineous family from Turkiye, who has been suffering from NDDs with two distinct clinical presentations. Methods and results: Combined in-depth genetic approaches led us to identify a homozygous frameshift variant in NALCN related to NDD and expansion of dodecamer repeat in CSTB related to Unverricht-Lundborg disease (ULD). Additionally, we sought to functionally analyze the NALCN variant in terms of mRNA expression level and current alteration. We have both detected a decrease in the level of premature stop codon-bearing mRNA possibly through nonsense-mediated mRNA decay mechanism and also an increased current in patch-clamp recordings for the expressed truncated protein. Conclusion: In conclusion, increased consanguinity may lead to the revealing of distinct rare neurogenetic diseases in a single family. Exome sequencing is generally considered the first-tier diagnostic test in individuals with NDD. Yet we underline the fact that customized approaches other than exome sequencing may be used as in the case of ULD to aid diagnosis and better genetic counseling.
Keywords: CSTB; Exome Sequencing; Linkage Analysis; Long PCR; NALCN; Neurodevelopmental Disorders